2010
DOI: 10.1029/2010jd013822
|View full text |Cite
|
Sign up to set email alerts
|

Air‐lake exchange of methane during the open water season in Syowa Oasis, East Antarctica

Abstract: [1] Dissolved methane (DM) concentrations were measured in 17 lakes as part of the operations of the 45th Japanese Antarctic Research Expedition in ice-free rocky areas along the eastern coast of Lützow-Holm Bay (Syowa Oasis) in East Antarctica in the summer of [2003][2004]. DM at the surfaces of 14 lakes ranged from the atmospheric equilibrium concentration (about 4 nmol L −1 for freshwater) to 385 nmol L −1 . Relatively low DM of less than 50 nmol L −1 were observed in about 60% of the lakes. Many of the lak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Sasaki et al, (2009Sasaki et al, ( , 2010 reported that approximately two-times larger flux from frozen bubbles (ebullition) in lake ice than diffusive methane flux during the open water season is released in Syowa Oasis, east Antarctica. Bastiviken et al, (2004) also reported that estimated total methane flux (ebullition + diffusion + storage) from all Swedish lakes (95,762) was 105 Gg CH 4 yr -1 and that the flux corresponded to 5~10% of total flux from wetlands.…”
Section: Uncertainties In the Methods Used In This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Sasaki et al, (2009Sasaki et al, ( , 2010 reported that approximately two-times larger flux from frozen bubbles (ebullition) in lake ice than diffusive methane flux during the open water season is released in Syowa Oasis, east Antarctica. Bastiviken et al, (2004) also reported that estimated total methane flux (ebullition + diffusion + storage) from all Swedish lakes (95,762) was 105 Gg CH 4 yr -1 and that the flux corresponded to 5~10% of total flux from wetlands.…”
Section: Uncertainties In the Methods Used In This Studymentioning
confidence: 99%
“…The procedure used for water sampling in 2008 was the same as that described in our previous paper (Sasaki et al, 2010). The water samples were gently poured in 500 mL glass vials, which were first washed by strong shaking with 100~200 mL of sampled water.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…The result of A-N analysis is shown in Table 2. Total area of all (1,269) lakes in Hokkaido is 809 km 2 . Average lake to land area ratio is 1.03%, which is about 1/3 of global average (2.8% estimated by Downing et al [9]).…”
Section: Estimations and Discussion Ofmentioning
confidence: 99%
“…[10]). And this average flux density is about five times greater than that from lakes in Syowa Oasis, in East Antarctica [2],…”
Section: Estimations Of Annual Methane Flux From Lakes In Hokkaidomentioning
confidence: 99%
See 1 more Smart Citation